Neurotological symptoms and academic performance of university students Sintomas otoneurológicos e desempenho acadêmico de estudantes universitários - Marcia Mattos Marques; Mauricio Malavasi Ganança; Carolina Mattos Marques; Fernando Freitas Ganança; Heloisa Helena Caovilla (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To compare the academic performance of university students with or without neurotological symptoms. METHOD: 100 students enrolled in the Biomedical Sciences Graduate School - Medical Modality of UNIFESP-EPM in 2007 and answered a neurotological screening questionnaire. RESULTS: The symptoms presented once, sometimes, many times or always, in a decreasing order of prevalence, were headache (74.0%), difficulty with concentration (57.0%), lack of memory (45.0%), physical indisposition, nausea /dizziness when in moving vehicle (37.0%), fainting (27.0%), nausea (26.0%), sensation of fullness in the ear (26.0%), hypersensitivity to sounds (26.0%), tinnitus (22.0%), vertigo and other kinds of dizziness (21.0%), imbalance when walking (21.0%), difficulty in hearing (21.0%), imminent sensation of fainting (11.0%) and vomiting (8.0%), alone or in different associations; convulsion was not mentioned. The final academic performance score ranged from 5.1 to 10.0. CONCLUSION: University students with or without neurotological symptoms have manifested similar academic performance. OBJETIVO: Comparar o rendimento escolar de universitários com e sem sintomas otoneurológicos. MÉTODO: Cem alunos matriculados e ativos no Curso de Graduação em Ciências Biomédicas - Modalidade Médica da UNIFESP-EPM em 2007 responderam um questionário de triagem otoneurológica. RESULTADOS: Os sintomas presentes uma vez, algumas vezes, muitas vezes ou sempre, em ordem decrescente de prevalência, foram: dor de cabeça (74,0%), dificuldade de concentração (57,0%), dificuldade de memória (45,0%), mal-estar/enjôo/tontura em veículos em movimento (37,0%), desmaio (27,0%), enjôo (26,0%), sensação de ouvido tapado (26,0%), hipersensibilidade a sons (26,0%), zumbido (22,0%), vertigem ou outros tipos de tontura (21,0%), desequilíbrio ao andar (21,0%), dificuldade para ouvir (21,0%), sensação de desmaio iminente (11,0%) e vômito (8,0%), isoladamente ou em diferentes combinações; convulsão não foi referida. As notas da avaliação final dos alunos foram variáveis entre 5,1 e 10,0. CONCLUSÃO: Estudantes universitários com ou sem sintomas otoneurológicos apresentaram rendimento escolar semelhante.